Drawn by the bison: Late Prehistoric native migration in the Central Plains - Ritterbush, Lauren W. (My University, 2002)
Popular images of the Great Plains frequently portray horse-mounted Indians engaged in dramatic bison hunts. The importance of these hunts is emphasized by the oft-mentioned dependence of the Plains Indians on bison. This animal served as a source of not only food but also materials for shelter, clothing, containers, and many other necessities of life. Pursuit of the vast bison herds (combined with the needs of the Indians' horses for pasturage) affected human patterns of subsistence, mobility, and settlement. The Lakota and Cheyenne, for instance, are described as relying heavily on bison meat for food and living a nomadic lifestyle in tune with the movements of the bison. More sedentary farming societies, such as the Mandan, Hidatsa, Pawnee, Oto, and Kansa, incorporated seasonal long-distance bison hunts into their annual subsistence, which also included gardening. In each case, multifamily groups formed bands or tribal entities of some size that cooperated with one another during formal bison hunts and other community activities. Given the importance of bison to these people living on the Great Plains, it is often assumed that a similar pattern of utilization existed in prehistory. Indeed, archeological studies have shown that bison hunting was key to the survival of Paleoindian peoples of the Plains as early as 11,000 years ago. If we combine archeological information about this very early period of prehistoric existence with documentation of the historic era, it seems plausible to interpret that focused bison hunting was the mainstay of Indian societies throughout the millennia of native occupation of the Plains. Upon close examination of the archeological record, however, we find that bison hunting was not equally important to all past Plains societies. During the Late Prehistoric period (A.D. 1000-1500), for instance, indigenous societies of the Central Plains were not heavily reliant on bison hunting. These societies organized themselves around individual households and depended on the harvesting of a wide variety of locally available wild and domestic resources. This pattern of subsistence, with limited interest in bison, proved successful given the small-scale social organization of these societies. A change toward more focused bison hunting developed in the Central Plains late in prehistory, not by indigenous Plains populations but by groups that migrated into the region in the thirteenth or fourteenth century. These immigrants came from the east and were likely Siouan rather than Caddoan speakers. They organized themselves in groups (villages) of linked households. Archeologists refer to this cultural manifestation as the Oneota tradition. With the entry of Oneota peoples into the Central Plains, indigenous households shifted their settlements, making room for the more cohesive and potentially aggressive population.
Keywords: Migration; Bison; Central Plains; Oneota; Central Plains tradition